Interlanguage in recount writing text on 8th grade secondary school student - Deadora Rahma Muthia; Fahriany Fahriany; Meli Aulia Utami (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2021)
This study attempts to analyze interlanguage production made by ten eight-grade students who were enrolled in one of the secondary schools in Jakarta. Interlanguage happens when a learner talk in the target language but their linguistic framework is still the source language (any prior language they knew beforehand). It is intended to explore kinds of interlanguage that occur in their recount writing and to explain the potentials of why the errors emerge in their recount writing. The data of the study requires one recount text writing produced by the participants of this present study. This study employed a qualitative research design and it was specifically presented using a descriptive case study. Furthermore, document analysis is employed as the procedure of collecting data when analyzing the writing. The result of the study showed that based on students' recount writing, the interlanguage is detected from the way they formed passive sentences, incorrect verb agreement, unparalleled sentences, and L1 to L2 translation. In that sense, it can be concluded that interlanguage happens due to L1 tendency which still dominated the students' minds when producing the target language. Thus, the students should be assisted to practice the correct rules of English in their writing, especially in recount text to prevent any possible fossilization.